2018
DOI: 10.1080/01431161.2018.1552818
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal characteristics and removal methodology of suspended particulate matter speckles from Geostationary Ocean Color Imager data

Abstract: Reviewing six years of Geostationary Ocean Color Imager (GOCI) suspended particulate matter (SPM) concentration images from 2011 to 2016 revealed unexpected and some enormously high or low values. These speckles are randomly scattered throughout the entire study area or congregated at a certain part, which has strongly restricted the scientific applications of GOCI data thus far. They can be classified into four types: isolated, near-cloud, patchtype, and slot-related speckles, based on spatial distribution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In contrast, the MFNN method exhibited high performance capability with regard to the abnormal pixel removal by eliminating 45% of the original pixels (Figure 14d). Previous studies have reported the high performance of the threshold-based scheme for removal speckles in ocean color images [14,16]. The accuracy obtained from the confusion matrix of the threshold method based on the spatial uniformity within 3 × 3 pixels was 91.7% for the image obtained on 13 January 2015 ( Figure 14).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In contrast, the MFNN method exhibited high performance capability with regard to the abnormal pixel removal by eliminating 45% of the original pixels (Figure 14d). Previous studies have reported the high performance of the threshold-based scheme for removal speckles in ocean color images [14,16]. The accuracy obtained from the confusion matrix of the threshold method based on the spatial uniformity within 3 × 3 pixels was 91.7% for the image obtained on 13 January 2015 ( Figure 14).…”
Section: Discussionmentioning
confidence: 86%
“…In addition, high-altitude aerosol conditions around cloud edges are likely to be different from the aerosol type of the background field especially in the open ocean, which makes it difficult to choose the proper aerosol model in the atmospheric correction procedure. This type of improper selection in the aerosol models may also lead to the emergence of an unexpected low chl-a concentration distribution [16]. Thus, the spectral characteristics of such erroneous pixels should be investigated.…”
Section: Abnormal Chlorophyll-a Features Around Cloudsmentioning
confidence: 99%
See 2 more Smart Citations
“…where NRTI refers to normalized RTI. Before applying the NRTI to GOCI, speckles in the GOCI images were first removed by using data on SPM [34] and then calculated chlorophyll-a concentration [52,53] using a 3-band ocean color algorithm (called OC3 algorithm) ( Figure 7). Pixels with negative values of R rs (λ) were regarded as failures of atmospheric correction and replaced with NaN values.…”
Section: Development Of a New Normalized Red Tide Intensity Index (Nrti)mentioning
confidence: 99%